Who can best recruit to randomized trials? Randomized trial comparing surgeons and nurses recruiting patients to a trial of treatments for localized prostate cancer (the ProtecT study). - Donovan, J; Peters, T; Noble, S; Powell, P; Gillatt, D; Oliver, SE; Lane, J; Neal, D; Hamdy, F (2003)
BACKGROUND AND OBJECTIVE: Recruitment to randomized trials is often difficult, but few studies have investigated interventions to improve recruitment. In a randomized trial nested within a trial of treatments for localized prostate cancer, we investigated the comparative effectiveness and cost-effectiveness of nurses and surgeons in recruiting patients. METHODS: Men with localized prostate cancer were randomized to see a nurse or urologic surgeon for an "information appointment" in which they were asked to consent to the ProtecT treatment trial comparing surgery, radiotherapy, and active monitoring. Analysis was conducted by intention to treat using chi-square with 95% confidence intervals for proportions and differences between groups. An economic evaluation was performed using the duration of appointments and grade of recruitment staff. RESULTS: Case-finding identified 167 men with localized prostate cancer. One hundred fifty (90%) took part in the recruitment trial. There was a 4.0% difference between nurses and surgeons in recruitment rates (67% nurses, 71% urologists, 95% CI -10.8% to +18.8%, P=.60). Cost-minimization analysis showed that nurses spent longer times with patients but surgeon costs were higher and nurses often supported surgeon-led clinics. CONCLUSION: Nurses were as effective and more cost-effective recruiters than urologic surgeons. This suggests an increased role for nurses in recruiting patients to randomized trials.